A novel triplex real-time PCR assay for the differentiation of lumpy skin disease virus, goatpox virus, and sheeppox virus - Nan, Wenlong; Gong, Mingxia; Lu, You; Li, Jinming; Li, Lin; Qu, Hailong; Liu, Chunju; Wang, Ying; Wu, Faxing; Wu, Xiaodong; Wang, Zhiliang; Chen, Yiping; et al. (Frontiers in Veterinary Science, 2023)
Introduction Three members of Capripoxvirus (CaPV) genus, including lumpy skin disease virus (LSDV), goatpox virus (GTPV), and sheeppox virus (SPPV), are mentioned as notifiable forms by World Organization for Animal Health. These viruses have negatively impacted ruminant farming industry worldwide, causing great economic losses. Although SPPV and GTPV cause more severe clinical disease in only one animal species, they can transfer between sheep and goats. Both homologous and heterologous immunization strategies are used to protect animals against CaPVs. However, development of accurate and rapid methods to distinguish these three viruses is helpful for the early detection, disease surveillance, and control of CaPV infection. Therefore, we developed a novel triplex real-time PCR (qPCR) for the differentiation of LSDV, GTPV, and SPPV. Methods Universal primers were designed to detect pan-CaPV sequences. Species-specific minor groove binder (MGB)-based probes were designed, which were labeled with FAM for LSDV, HEX for GTPV, and ROX for SPPV. The sensitivity, specificity, reproducibility, and ability of detecting mixed infections were evaluated for the triplex qPCR. Further, 226 clinical samples of the infection and negative controls were subjected to the triplex qPCR, and the results were verified using PCR-restriction fragment length polymorphism (PCR-RFLP) and sequencing methods for PRO30 gene. Results The triplex qPCR could successfully distinguish LSDV, GTPV, and SPPV in one reaction, and the assay sensitivity was 5.41, 27.70, and 17.28 copies/μL, respectively. No cross-reactivity was observed with other viruses causing common ruminant diseases, including des petits ruminants virus, foot-and-mouth disease virus, bluetongue virus, ovine contagious pustular dermatitis virus, infectious bovine rhinotracheitis virus, and bovine viral diarrhea-mucosal disease virus. Inter-and intra-assay variabilities were < 2.5%. The results indicated that the triplex qPCR was highly specific, sensitive, and reproducible. Simulation experiments revealed that this assay could successfully distinguish two or three viruses in case of mixed infections without any cross-reaction. For clinical samples, the results were completely consistent with the results of PCR-RFLP and sequencing. This demonstrated that the assay was reliable for clinical application. Discussion The triplex qPCR is a robust, rapid, and simple tool for identifying various types of CaPV as it can successfully distinguish LSDV, GTPV, and SPPV in one reaction. Furthermore, the assay can facilitate more accurate disease diagnosis and surveillance for better control of CaPV infection.